BREAKING THE LABEL: DEVELOPMENT OF ULTRA-PROCESSED-FOOD INTERACTIVE EDUCATIONAL VIDEO TO IMPROVE NUTRITION LITERACY AND HEALTHY FOOD SELECTION IN STUDENTS - Valentina Wiyanda Ratu Pratikno; Zahra Anggita Pratiwi; Agung Wibowo; Aprinia Dian Nurhayati (Jurnal Gizi dan Pangan Soedirman, 2026)
Consumption Ultra-Processed Food (UPF) in students is classified as high as 50.3%, although as many as 48% of students have good UPF knowledge and 61.7% of students have the habit of reading food labels. This shows that good knowledge is not always directly proportional to healthy food consumption patterns. This research aims to develop interactive educational videos "Breaking The Label" related to UPF as a solution to increase understanding that can change the attitude of choosing healthy food in students. The media development method uses Research and Development (R&D) with design pre-experiment one group pre-test-post-test. The development model used is ADDIE which is carried out in 4 stages, including analysis, planning, development and implementation involving 36 students of the State University of Malang selected using techniques non probability sampling by the convenience sampling. In its implementation from the results of validation tests by subject matter experts showed that S-CVI 0.70 was categorized as valid and the results of the validation test by media experts showed that S-CVI 1.00 was categorized as valid. The interactive educational videos developed are declared feasible as educational media. The results of the analysis showed an increase in the average nutritional literacy score before intervention (24.67) and after intervention (27.58) with p = < 0.001 and an increase in the average score of healthy food selection attitude before intervention (6.72) and after intervention (7.97) with p = < 0.001.